HUBUNGAN PROGRAM HACCP DENGAN PRAKTIK KESELAMATAN DAN KESEHATAN KERJA DAN WORKPLACE HAZARD PADA PEKERJA INSTALASI GIZI DIRUMAH SAKIT ISLAM SULTAN AGUNG, SEMARANG - Muhammad Thoha; Daru Lestantyo; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The healthcare industry sectors that roled in health service by employed huge amount of workers. HACCP is a food safety system to identified hazards in a food production line to distribution to patients so that patients get nutrition as needed and avoided the impact of contamination in these patient. The safety of nutritional installation workers was very influential in the success of the HACCP Program Implementation to minimize the occurrence of accidents or nearmiss to workers, production, work environment and patients. The purpose of this research was to analyzed the relations of occupational health and safety practices on nutritional installation workers and workplace hazard with the HACCP Program Implementation. The independent variable in this research was the implementation of HACCP program with dependent variable such as knowledge, worker attitude, worker commitment and practice of SOP implementation and there are intervening variable such as age, gender and education level. The type of this research is descriptive analytics with cross-sectional design. The sample in this research is 32 respondent of food handling workers of nutrient installation with sampling method, total sampling. Statistical analysis was done by Chi-Square test. The result of this research showed that the HACCP program-related and influential in the knowledge, worker attitude, worker commitment and good SOP implementation practice. In this research, the hospital should provide an opportunity for nutritional installation workers to express their opinion about SOP, place SOP on each part of nutrition installation.